LEAN SIX SIGMA APPROACH FOR LABOR PRODUCTIVITY IMPROVEMENT AT FINAL TEST SEMICONDUCTOR MANUFACTURING - M.A.R, Md Nizam; A., Rohana; J.K., Norlymalis, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Labor productivity improvement is all about getting more units out with the same or lesser amount of labor. Due to the economic downturn, the semiconductor company under study wanted to determine the ideal number of operators to be employed especially at the critical operations in order to minimize the labor cost and improve labor productivity. Thus, the main focus of the study is to perform analysis at the bottleneck area in order to determine the labor utilization and also toidentify the ideal man to machine ratio at the semi-automatic final test operation. The lean work study analysis using Process Mapping and Maynard Operational Sequence Technique (MOST) also enabled the authors to unveil the various types of wastes occurring at the final test area in order to propose lean improvement activities. Six Sigma Define, Measure, Analyze, Improve and Control (DMAIC) approach was employed during the implementation of the study.The results of the final test area Lean Six Sigma study showed significant improvements could be made on the labor utilization and man to machine ratio. With the knowledge of how to improve the labor productivity, the semiconductor company will be on the right track towards achieving a leaner and more cost effective operation.